ANALYSIS AND DEVELOPMENT POSSIBILITIES OF BUSINESS INCUBATORS IN LATVIA - Arbidāne, Iluta; Tarasova, Madara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The nature of business incubators and their historical development in the world and in Latvia, the role in the global and Latvia's economy, the requirements set by the Investment and Development Agency of Latvia (LIAA) for the operators and enterprises of business incubators within the framework of the activity “Business Incubators” (implemented within the project “Development of Business Incubators in Latvia” co-funded by the European Regional Development Fund), as well as the results achieved by the business incubators and enterprises, and their future perspectives are covered in the research. The aim of the study is to explore and analyse the implementation and performance of the LIAA’s activity "Business incubators" in Latvia. The main issues analysed in the paper are the implementation conditions, the results, and analysis of the activity “Business Incubators” administered by the LIAA, as well as its effect upon the business activity in Latvia. Based on the obtained results, the authors conclude that the continuation of the business incubators' operation is a precondition for development of innovative business and growth of the economy of Latvia.